Clinical and pharmaco-economic assessment of ACE inhibitors perindopril and enalapril in coronary heart disease patients after coronary artery bypass graft surgery - Yu. M. Lopatin; E. P. Dronova (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To perform clinical and pharmaco-economic assessment of long-term therapy with ACE inhibitors perindopril and enalapril in coronary heart disease (CHD) patients after coronary artery bypass graft (CABG) surgery.Material and methods. This prospective, randomized clinical trial included 250 CHD patients. Group I (n=125) received perindopril, Group II (n=125) — enalapril. The follow-up period lasted for three years after CABG intervention. All participants received standard CHD therapy.Results. Comparing to enalapril, perindopril demonstrated improved left ventricular systolic function, increased physical stress tolerance, and reduced frequency of ischemic episodes.Conclusion. In CHD patients after CABG, perindopril therapy is more clinically efficient and cost-effective than enalapril treatment.